Validated LC-MS/MS Method for the Determination of Mirodenafil in Rat Plasma and its Application to a Comparative Pharmacokinetic Study of the Free Base and Hydrochloride Salt Forms of Mirodenafil - Kim, T. K.; Yoo, H. H.; Park, J. H. (Arzneimittelforschung, 2012)
In this study, the pharmacokinetics of 2 forms of mirodenafil, namely the base form and the hydrochloride salt form, were investigated in rats. The 2 forms were orally administered to rats and the plasma concentrations of mirodenafil were determined using liquid chromatography-tandem mass spectrometry (LC-MS/MS). The mirodenafil base and hydrochloride salt forms showed similar pharmacokinetic profiles in terms of their maximum plasma concentration (Cmax) and area under the concentration-time curve (AUC). The time to peak concentration (Tmax) of the base form was slightly greater than that of the salt form, but this difference was not statistically significant. These results suggest that the mirodenafil base and hydrochloride forms are pharmacokinetically equivalent in rats, and thus the base form could be used in various mirodenafil formulations as a substitute for the existing mirodenafil hydrochloride form.
Keywords: mirodenafil; comparative pharmacokinetics; rats; LC-MS/MS